2015
DOI: 10.1038/srep17395
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of glucokinase regulatory protein decreases glucose metabolism by suppressing glucokinase activity

Abstract: Glucokinase (GK), mainly expressed in the liver and pancreatic β-cells, is critical for maintaining glucose homeostasis. GK expression and kinase activity, respectively, are both modulated at the transcriptional and post-translational levels. Post-translationally, GK is regulated by binding the glucokinase regulatory protein (GKRP), resulting in GK retention in the nucleus and its inability to participate in cytosolic glycolysis. Although hepatic GKRP is known to be regulated by allosteric mechanisms, the prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 54 publications
1
34
0
Order By: Relevance
“…Similar to several other sirtuins, SIRT2 is involved in energy homeostasis (126). For instance, it deacetylates glucokinase (GK) (127) and phosphoenolpyruvate carboxykinase (PEPCK) (128), destabilizing the former but stabilizing the latter. GK facilitates glucose phosphorylation, the first step leading to glycolysis and glycogenesis, and PEPCK is a rate‐limiting enzyme of gluconeogenesis.…”
Section: Sirt2mentioning
confidence: 99%
“…Similar to several other sirtuins, SIRT2 is involved in energy homeostasis (126). For instance, it deacetylates glucokinase (GK) (127) and phosphoenolpyruvate carboxykinase (PEPCK) (128), destabilizing the former but stabilizing the latter. GK facilitates glucose phosphorylation, the first step leading to glycolysis and glycogenesis, and PEPCK is a rate‐limiting enzyme of gluconeogenesis.…”
Section: Sirt2mentioning
confidence: 99%
“…GKRP is responsible for the regulation of hepatic glucose metabolism by controlling an activity and cellular localization of glucokinase – an enzyme that phosphorylates glucose, preparing it for glycogen synthesis or glycolysis . It has been demonstrated that polymorphism or acetylation of GKRP were associated with type 2 diabetes . Similarly, the diminished expression of GYS2 – a protein engaged in glycogen biosynthesis – was observed in patients with type 2 diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…In the liver, GCKR forms an inhibitory complex with GCK, the enzyme responsible for regulating the uptake and storage of dietary glucose [15]. The glucokinase Associations between glucokinase and glucokinase regulatory protein gene polymorphisms and clinical parameters in pregnant women regulatory protein regulates hepatic GCK activity competitively with respect to the substrate glucose, the phosphate esters fructose 6-and fructose 1-phosphate, which enhance or inhibit the action of the regulatory protein, respectively [16,17].…”
Section: Discussionmentioning
confidence: 99%